(untitled) (Journal of Parents and Teachers, 2024)
The article is about adapting to the new education law, which has led to the implementation of quarterly report cards. These report cards reflect the progress made during the months of work and learning, focusing on the concepts, attitudes, and habits developed by each student individually.